Contribution of dopamine receptors to periaqueductal gray-mediated antinociception - Meyer, Paul J. (2009)
RATIONALE: Morphine relieves pain, in part, by acting on neurons within the periaqueductal gray (PAG). Given that the PAG contains a subpopulation of dopamine neurons, dopamine may contribute to the antinociceptive effects mediated by the PAG. METHODS: This hypothesis was tested by measuring the behavioral and electrophysiological effects of administering dopamine agonists and antagonists into the ventrolateral PAG (vPAG). An initial histological experiment verified the existence of dopamine neurons within the vPAG using dopamine transporter and tyrosine hydroxylase antibodies visualized with confocal microscopy. RESULTS: Microinjection of cumulative doses of morphine into the vPAG caused antinociception that was dose-dependently inhibited by the dopamine receptor antagonist α-flupenthixol. α-Flupenthixol had no effect on nociception when administered alone. Injection of the dopamine receptor agonist (-) apomorphine into the vPAG caused a robust antinociception that was inhibited by the D2 antagonist eticlopride but not the D1 antagonist SCH-23390. The effects of dopamine on GABA(A)-mediated evoked inhibitory post-synaptic potentials (eIPSCs) were measured in PAG slices. Administration of met-enkephalin inhibited peak evoked inhibitory post-synaptic potentials (eIPSCs) by 20-50%. Dopamine inhibited eIPSC by approximately 20-25%. Administration of α-flupenthixol (20 μM) attenuated eIPSC inhibition by dopamine, but had no effect on met-enkephalin-induced inhibition. CONCLUSIONS: These data indicate that PAG dopamine has a direct antinociceptive effect in addition to modulating the antinociceptive effect of morphine. The lack of an effect of α-flupenthixol on opioid-inhibition of eIPSCs indicates that this modulation occurs in parallel or subsequent to inhibition of GABA release.